Advances in Epidemic Control Laws & COVID-19 Pandemic in India: A Medico-Legal Analysis - M.Z.M. Nomani; Faisal Sherwani; Jalal Allail (Indian Journal of Forensic Medicine & Toxicology, 2021)
This paper deals with the efficacy of the Epidemic Diseases Act, 1897 and Epidemic Diseases AmendmentAct, 1937 in the context of Covid-19 pandemic. The colonial mould of epidemic control laws reviewedthe World Health Organization (WHO) legal guidelines for disease preparedness and response. The publichealth strategies of epidemic-pandemic control need juristic innovation, and blanket application of Britishenactment fall short of the expectation of the right based approach health and equity. The enforcement ofthe Epidemic Diseases Act, 1897 during dengue, swine flu, influenza and COVID-19 criticized by the Indianmedico-legal community in India. The emerging discourse can be tailor-made to suit the magnitude of theCovid-19 and pandemics needs a careful analysis. Though the WHO Revision of the International HealthRegulations, 2005 offers new paradigm the Indian government resort to the Epidemic Diseases AmendmentOrdinance, 2020 needs a critical appraisal in COVID-19 pandemic in India.